2014
DOI: 10.1371/journal.pone.0106468
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Cognitive Control in Language Switching: An fMRI Study of English-Chinese Late Bilinguals

Abstract: The present study explored the bilingual cognitive control mechanism by comparing Chinese-English bilinguals’ language switching in a blocked picture naming paradigm against three baseline conditions, namely the control condition (a fixation cross, low-level baseline), single L1 production (Chinese naming, high-level baseline), and single L2 production (English naming, high-level baseline). Different activation patterns were observed for language switching against different baseline conditions. These results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Note that some previous studies presented the language cue simultaneously with the stimulus (e.g., Abutalebi et al, , 2013Garbin et al, 2011;Guo et al, 2011) whereas others, including this study, presented the cue slightly before the stimulus (200-400 msec; e.g., Ma et al, 2014;Hernandez, 2009;Wang et al, 2007Wang et al, , 2009Hernandez et al, 2000Hernandez et al, , 2001. We think that both approaches have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Note that some previous studies presented the language cue simultaneously with the stimulus (e.g., Abutalebi et al, , 2013Garbin et al, 2011;Guo et al, 2011) whereas others, including this study, presented the cue slightly before the stimulus (200-400 msec; e.g., Ma et al, 2014;Hernandez, 2009;Wang et al, 2007Wang et al, , 2009Hernandez et al, 2000Hernandez et al, , 2001. We think that both approaches have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 67%
“…One possible interpretation for the absence of the caudate in the current study is that it is a consequence of the use of three different languages and the associated distribution of switch and repeat trials in the different languages. In a recent study, Ma et al (2014) found the caudate when contrasting the switch condition with a simple naming condition in L1. However, the caudate was not observed when comparing the switch condition with a simple naming condition in L2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Right-lateralized activity in the caudate nucleus has been reported during a language switching task in Chinese-English bilinguals (Ma et al 2014) and, in a meta-analysis of language switching studies, Luk et al (2012) showed the implication of both right and left striatal structures.…”
Section: Discussionmentioning
confidence: 93%
“…Such an interpretation is supported by the contractions seen in the bilateral thalamus, which indicates a decreased reliance on this structure with increased efficiency in language selection (19,31). The left caudate nucleus is more often implicated in language and task-switching cognitive demands (6); however, several studies report recruitment of the right caudate for more demanding language-switching tasks (59,60). Regarding the predictions of the ACH, we may interpret the right caudate and thalamic contractions as a marker of decreased requirements for gating the interfering language.…”
Section: Discussionmentioning
confidence: 99%